ANALISIS FEEDER SYSTEM MENUJU HALTE MUSI II TRANSMUSI KORIDOR VI KOTA PALEMBANG - Sukarman Sukarman (PILAR, 2013)
A city will continue developing as long as there are activities in it. City development occurs due to the movement of people in carrying out the activities. The transportation system plays a very important role in supporting the movement of the people.Palembang as the Capital of South Sumatra Province, which is one of the centers of development, also relies on a transportation system for its development. The Settlement areas or housing areas grow everywhere with diffuse and irregular patterns. This leads to widespread demand for transportation. This condition is not easy for the public transport to serve, consequently the transport system used is predominantly private vehicles. Of course, the transportation system of this characteristic has broad impact on various aspects of life and urban environment.  With the operation of transmusi buses, it is deemed necessary to study the transport feeder suitable for connecting the centers of settlements on the outskirts towards the path through which the transmusi buses run, so that the performance of transmusi buses can be optimized and the use of private vehicles in urban areas can be minized.     The objective of this study is to develop a pattern of feeder transport services from residential location towards the transmusi bus stops along the routes of transmusi buses in Palembang, especially for the people living in the Sub-district of Gandus  towards transmusi bus stop of Musi II. The method of study used is a descriptive method using a survey. The result of this study is to develop transport feeder from the settlement areas towards the Musi II bus stop by considering the habits of the people,  the public demand, and the characteristics of the region. It will be the development of pedestrian facilities as far as 1 km from the bus stop, especially on the roads through which the heavy vehicles run, parking lots area for motorcycles of  5,682 m2,  sufficient public transport, bus stop of medium size. The conclusion made is to respond to the pattern of sprawl (dispersed settlement) on the outskirts of the city. It is necessary to have a transport systems using feeder -line haul system (feeder-main freight transport). The main transport in urban areas is transmusi bus while freight feeder bus from the settlement towards transmusi bus stop is a variety of modes commonly owned and used by the community all this time with some improvement and additional facilities required.